Activation of Caenorhabditis elegans Levamisole-Sensitive and Mammalian Nicotinic Receptors by the Antiparasitic Bephenium - Turani, Ornella (2018)
Nicotinic acetylcholine receptors (nAChRs) are ligand-gated ion channels involved in neuromuscular transmission. In nematodes, muscle nAChRs are targets of antiparasitic drugs. Bephenium is an anthelmintic compound whose molecular action in the free-living nematode Caenorhabditis elegans, which is a model for anthelmintic drug discovery, is poorly known. We explored the effect of bephenium on C. Elegans locomotion and applied single-channel recordings to identify its molecular target, mechanism of action, and selectivity between mammalian and C. Elegans nAChRs. As in parasites, bephenium paralyzes C. Elegans. A mutant strain lacking the muscle levamisolesensitive nAChR (L-AChR) shows full resistance to bephenium, indicating that this receptor is the target site. Bephenium activates L-AChR channels from larvae muscle cells in the micromolar range. Channel activity is similar to that elicited by levamisole, appearing mainly as isolated brief openings. Our analysis revealed that bephenium is an agonist of L-AChR and an open-channel blocker at higher concentrations. It also activates mammalian muscle nAChRs. Opening events are significantly briefer than those elicited by ACh and do not appear in activation episodes at a range of concentrations, indicating that it is a very weak agonist of mammalian nAChRs. Recordings in the presence of ACh showed that bephenium acts as a voltagedependent channel blocker and a low-affinity agonist. Molecular docking into homology-modeled binding-site interfaces represent the binding mode of bephenium that explains its partial agonism. Given the great diversity of helminth nAChRs and the overlap of their pharmacological profiles, unraveling the basis of drug receptor-selectivity will be required for rational design of anthelmintic drugs.